ANALISIS KONTEN VISUAL: STIGMA OBESITAS DALAM PORTAL BERITA ONLINE LOKAL INDONESIA - Najma Najma; S. Kunto Adi Wibowo; Ikhsan Fuady (Metacommunication: Journal of Communication Studies, 2022)
Negative stigmatization of obese people is often found in everyday life. This is reinforced by the role of the media, especially news, which internalizes and builds public perception. This study was conducted to determine how obese people are depicted in the visual content of 5 local online news portals in Indonesia, how to compare the depiction of obese and non-obese people, and to examine whether there is still an element of obesity stigmatization in the visual content of local online news in Indonesia. The study was conducted by collecting photo samples from 5 local online news portals in Indonesia for 6 months, starting from October 2021 to March 2022 that met the criteria (n = 180) and determining the number of samples using the monkey survey website (n = 123). Furthermore, the photos will be encoded by the coders which are then analyzed using descriptive and inferential tests with non-parametric statistical calculations chi-square Independence Test using Statistical Product and Service Solutions (SPSS) software. The results show that 37.5% of Indonesian local online news visual content is still stigmatized. Obese people were 53.65% more likely to be described as male and 94.4% more likely to be described as young. When compared with non-obese depictions, obese people tended to be disproportionately more likely to be depicted (80%), undressed or bare stomach (79%), and sedentary behaviors (65%), such as watching TV, sleeping, eating, and others activities with minimal mobilization.Keywords:  Obesity Stigma, Online News Portal, Visual Content.